2020
DOI: 10.1136/bmj.m1176
|View full text |Cite
|
Sign up to set email alerts
|

Bridging the quality gap in diagnosis and treatment of malaria

Abstract: Controlling and eliminating malaria will require intensified efforts to improve the quality of diagnosis and treatment argue Daniel Ikeda and colleagues

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 24 publications
(24 reference statements)
0
6
0
Order By: Relevance
“…But this study primarily focused on facility-level factors due to the lack of data on patient characteristics. Other single-country studies also explored the potential predictors of quality from the perspective of the health system, such as the availability of diagnostic tools, antimalarial medicines, and health workers [ 18 , 19 , 21 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…But this study primarily focused on facility-level factors due to the lack of data on patient characteristics. Other single-country studies also explored the potential predictors of quality from the perspective of the health system, such as the availability of diagnostic tools, antimalarial medicines, and health workers [ 18 , 19 , 21 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Drug-based therapy is the mainstream treatment measure. However, the increasing occurrence of antimalarial drug resistance, poor treatment access, and the lack of new antimalarial drugs pose severe challenges to successfully treating malaria. , There is an urgent need to develop new and effective pharmaceutical dosage forms for malaria therapy, particularly for CM treatment …”
Section: Introductionmentioning
confidence: 99%
“…7,8 There is an urgent need to develop new and effective pharmaceutical dosage forms for malaria therapy, particularly for CM treatment. 9 Nanocarriers are versatile tools to improve the pharmacokinetics of effective drugs by delivering drugs specifically to the pharmacological site of action. 10−12 Nanocarriers are increasingly being researched for malaria diagnosis, 13,14 therapeutics, 12 and vaccine formulation, 15 but the exploration of bionic cell membrane nanotechnology to treat malaria has never been reported.…”
Section: ■ Introductionmentioning
confidence: 99%
“…However, when a policy is implemented on a large scale under real-life conditions, the use of observational studies can be suitable and is often the only feasible option to identify both interventional and non-interventional determinants of performance [19]. Recent studies across Africa have suggested a variety of factors associated with health workers' compliance with the test-based management of malaria [8,[22][23][24]. However, these studies were commonly undertaken at a single point in time [8,22], focusing on only one of the outcomes (e.g.…”
Section: Introductionmentioning
confidence: 99%